(untitled) - Ohanian, Hans C. (Englewood Cliffs, NJ., 1987)
This text provides a smooth transition from introductory into modern physics--the physics of the 20th century. The mathematics is kept simple, so students can better concentrate on the important physical concepts.
Keywords: Physics,Vật lý